Persepsi Pasien dan Perawat tentang Patient Safety di Pelayanan Hemodialisa - Dewi Kusumastuti; Oryzati Hilman; Arlina Dewi (Jurnal Keperawatan Silampari, 2021)
This study aims to explore patient and nurse perceptions of patient safety to increase patient engagement so that patients can be aware of patient safety in the Hospital Hemodialysis Unit. This research method uses qualitative methods of conducting in-depth interviews with patients and medical personnel. The results of this study indicate that overall the patients said they were satisfied with the services provided; this was evidenced by the patient feeling very well known by the medical staff, both nurses and doctors. In conclusion, this kinship relationship is highly valued by the patient and accompanying family so that patients can be open to medical personnel so that effective communication can be well established. Keywords: Hemodialysis, Patient Engagement, Patient Safety